1978
DOI: 10.1152/ajpendo.1978.234.5.e489
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in steroid binding plasma proteins in Macaca nemestrina during pregnancy.

Abstract: We measured the corticosterone and dihydrotestosterone steroid binding capacities of corticosteroid-binding globulin (CBG) and sex steroid plasma binding protein (SBP) throughout pregnancy in seven Macaca nemestrina. The nSBP binding capacity rises significantly by 28 days of pregnancy, remains elevated through 56 days, tends to fall through midpregnancy, and then decreases dramatically to very low values 130-153 days after conception. In contrast, nCBG rises slightly (1.2-fold) in early pregnancy, is elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

1980
1980
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
1
9
0
1
Order By: Relevance
“…I t appears unlikely that plasma dilution during gestation affects the mSBP concentration since total plasma protein concentration is sustained. Moreover, as Schiller et al (1978) and Stanczyk et al (1986) have shown in rhesus monkeys, we have shown that estradiol gradually increased throughout pregnancy while total testosterone was maintained.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…I t appears unlikely that plasma dilution during gestation affects the mSBP concentration since total plasma protein concentration is sustained. Moreover, as Schiller et al (1978) and Stanczyk et al (1986) have shown in rhesus monkeys, we have shown that estradiol gradually increased throughout pregnancy while total testosterone was maintained.…”
Section: Discussionsupporting
confidence: 69%
“…mulatta, and Koritnik and Marschke (1986) in M. fasciculans have shown by binding assay that in nonhuman primates, the mSBP concentration is not elevated at term. These results have been confirmed by Schiller et al (1978), who investigated the possibility of the synthesis of a new binding protein by using steadystate polyacrylamide gel electrophoresis. We confirmed here that the concentration of the protein as an antigenic determinant was also reduced in 3 of the 4 pregnant females studied.…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations